How to assess chest wall deformity in children with pectus excavatum – evaluation of the agreement among methods - Kostić, Marko; Sretenović, Aleksandar; Savić, Milan; Popović, Marko; Kostić, Sanja; Stamenović, Davor (Vojnosanitetski pregled, 2021)
Background/Aim. Pectus excavatum (PE) is the most common deformity of the frontal aspect of the chest wall in children. A particular dilemma arises about the degree of deformity that should be subjected to surgical treatment. The aim of this study was to compare several morphological methods of evaluating the degree of deformity and determine the matching among them, as well as to determine the connection between the functional and morphological abnormalities of echocardiography. Methods. The study included 35 patients with PE, aged between 7 and 15 years. A noninvasive evaluation of chest deformity was carried out in all patients by photographic method (surrogate of clinical examination), native X-ray imaging, and computed tomography (CT), as well as by echocardiographic examination. Results. In our group of patients, males were more common (67.5%), as well as children with the Haller index (HI) > 3.5 [represented in most children (86.7%)]. A significant correlation of the index of the affected sternum segment (ASt) and the total length of the sternum (ASt/LSt) determined by the photographic method with that determined by the CT scan of the chest was established (p = 0.001). In addition, the correlation between HI, determined by the X-ray method and CT images was presented (p = 0.012). In contrast, despite the high frequency of echocardiographic abnormalities (69%), those were not mutually correlated with the degree of pronounced morphological deformities of the chest wall. Conclusion. A detailed clinical examination and photographic evaluation method, combined with the X-ray method, can determine the severity of deformity with a high degree of agreement with the CT chest findings. In this way, it is possible for children with PE, who are not candidates for surgical treatment, to be spared from repeated CT scans that are carried out in order to monitor the development of chest deformities with growth. Echocardiographic evaluation remains an integral part of the assessment of children with PE.